2006
DOI: 10.1074/jbc.m601035200
|View full text |Cite
|
Sign up to set email alerts
|

Formation of F-ring Isoprostane-like Compounds (F3-Isoprostanes) in Vivo from Eicosapentaenoic Acid

Abstract: Eicosapentaenoic acid (EPA, C20:5, -3) is the most abundant polyunsaturated fatty acid (PUFA) in fish oil. Recent studies suggest that the beneficial effects of fish oil are due, in part, to the generation of various free radical-generated non-enzymatic bioactive oxidation products from -3 PUFAs, although the specific molecular species responsible for these effects have not been identified. Our research group has previously reported that pro-inflammatory prostaglandin F 2 -like compounds, termed F 2 -isoprosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 40 publications
(42 reference statements)
2
99
0
3
Order By: Relevance
“…Interestingly, our laboratory has recently shown that the levels of IsoPs generated from the oxidation of EPA significantly exceed those of F 2 -IsoPs generated from arachidonic acid, perhaps because EPA contains more double bonds and is therefore more easily oxidizable (4). Additionally, in vivo in mice, levels of F 3 -IsoPs in tissues such as heart were virtually undetectable at base line, but supplementation of animals with EPA markedly increased quantities up to 27.4 Ϯ 5.6 ng/g of heart tissue.…”
Section: Formation Of Isops From Other Polyunsaturated Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, our laboratory has recently shown that the levels of IsoPs generated from the oxidation of EPA significantly exceed those of F 2 -IsoPs generated from arachidonic acid, perhaps because EPA contains more double bonds and is therefore more easily oxidizable (4). Additionally, in vivo in mice, levels of F 3 -IsoPs in tissues such as heart were virtually undetectable at base line, but supplementation of animals with EPA markedly increased quantities up to 27.4 Ϯ 5.6 ng/g of heart tissue.…”
Section: Formation Of Isops From Other Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…F-ring IsoPs have been shown to be generated from the peroxidation of linolenic acid (C18:3, -3, F 1 -IsoPs), EPA (C20:5, -3, F 3 -IsoPs), and DHA (C22:6, -3, F 4 -neuroprostanes) (Fig. 3, A and B) (4,5). Similar to the distribution of F 2 -IsoP regioisomers, certain F 3 -IsoP and F 4 -neuroprostane regioisomers are generated in greater amounts than others (40).…”
Section: Formation Of Isops From Other Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…In the course of performing such experiments, we also undertook studies to confirm the stability of EPA in the diet fed to mice to ensure that the source of oxidized EPA oxidation products was not the diet and that they had been generated in vivo. For these experiments, the AIN-93 diet containing EPA was quantified for F 3 -IsoPs at the beginning of the study and after its completion using the methods we have previously employed to quantify these compounds in animal tissues employing a stable isotope dilution gas chromatography MS assay (19). In addition, the diet was allowed to remain at room temperature under the same conditions as present in mouse cages for up to 7 days and F 3 -IsoPs measured.…”
Section: Identification Of Novel Oxidation Products From Epa In Vivo-mentioning
confidence: 99%
“…The aqueous layer was not acidified prior to the extraction. It should be noted that we have previously shown that this extraction approach does not lead to oxidation of arachidonate or EPA ex vivo (19,25). Basic hydrolysis was carried out in 0.5 ml of MeOH and 0.5 ml of 15% KOH at 37°C for 30 min.…”
Section: Ag ϩ Coordination Ionspray (Cis)-ms Analysis Of Oxidized Epamentioning
confidence: 99%
See 1 more Smart Citation